Drugs, addiction, and the brain - Koob, George F.; Arends, Michael A.; Le Moal, Michel (Academic Press, 2014)
Drugs, Addiction, and the Brain explores the molecular, cellular, and neurocircuitry systems in the brain that are responsible for drug addiction. Common neurobiological elements are emphasized that provide novel insights into how the brain mediates the acute rewarding effects of drugs of abuse and how it changes during the transition from initial drug use to compulsive drug use and addiction. The book provides a detailed overview of the pathophysiology of the disease. The information provided will be useful for neuroscientists in the field of addiction, drug abuse treatment provider.